Mega-events as economies of the imagination - Tzanelli, Rodanthi, 1974- author.
1 online resource
Keywords: Atmosphere, the elusive ambiance of a place, enables or hinders its mobility in global consumption contexts. Atmosphere connects to social imaginaries, utopian representational frames producing the culture of a city or country. But who resolves atmospheric contradictions in a place's social and cultural rhythms, when the eyes of the world are turned on it? Mega-Events as Economies of the Imagination examines ephemeral and solidified atmospheres in the Rio 2016 Olympic Games and the handover ceremony to Tokyo for the 2020 Games. Indeed, highlighting the various social and cultural implications upon these Olympic Games hosts, Tzanelli argues that the Olympic City' is produced by aesthetic "imagineers", mobile groups of architects, artists and entrepreneurs, who aesthetically engineer' native cultures as utopias. Thus, it is explored as to how Rio and Tokyo's "imagineers" problematize notions of creativity, cosmopolitan togetherness and belonging. Mega-Events as Economies of the Imagination will appeal to postgraduate students, postdoctoral researchers and professionals interested in fields such as: Globalization Studies, Mobility Theory, Cultural Sociology, International Political Economy, Conference and Event Management, Tourism Studies and Migration Studies.